1991
DOI: 10.1128/jcm.29.11.2543-2549.1991
|View full text |Cite
|
Sign up to set email alerts
|

Direct polymerase chain reaction test for detection of Helicobacter pylori in humans and animals

Abstract: We designed a polymerase chain reaction (PCR) for amplifying the Helicobacter pylori gene encoding 16S rRNA. Primers for the specific detection of H. pylori were designed for areas of the 16S rRNA gene in which there is the least sequence homology between H. pylori and its closest relatives. The specificity of detection was confirmed by ensuring that the primers did not amplify DNA extracts from the campylobacters H. cinaedi, H. mustelae, and Wolinela succinogenes, which are the closest relatives of H. pylori,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
2
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(125 citation statements)
references
References 36 publications
3
119
2
1
Order By: Relevance
“…Thus, a scrupulous analysis carried out in the present study to assess the status of the cag genes in ulcer patients and non-ulcer patients showed the prevalence of most of the genes of this intricate island in the DNA isolated from the saliva of the H. pylori infected subjects irrespective of their clinical status. The 16S rRNA amplification was carried out in the initial stages, along with the biopsy DNA, to confirm the presence of H. pylori in the saliva specimens of infected patients because 16S rRNA is the most conserved region to depict the presence of any organism 22 and also because of higher sensitivity and specificity of 16S rRNA primers to detect H. pylori in comparison with other primers specific to H. pylori. 14,23 Hence, in the present study, 16S rRNA amplification and histopathology were taken as a 'standard' to confirm active H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a scrupulous analysis carried out in the present study to assess the status of the cag genes in ulcer patients and non-ulcer patients showed the prevalence of most of the genes of this intricate island in the DNA isolated from the saliva of the H. pylori infected subjects irrespective of their clinical status. The 16S rRNA amplification was carried out in the initial stages, along with the biopsy DNA, to confirm the presence of H. pylori in the saliva specimens of infected patients because 16S rRNA is the most conserved region to depict the presence of any organism 22 and also because of higher sensitivity and specificity of 16S rRNA primers to detect H. pylori in comparison with other primers specific to H. pylori. 14,23 Hence, in the present study, 16S rRNA amplification and histopathology were taken as a 'standard' to confirm active H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Genes probed include those encoding urease: ureA; ureB and ureC [20]; and 16s ribosomal RNA. The latter can give a positive result with other Helicobacter species [30]. As a diagnostic tool PCR has two main advantages.…”
Section: Polymerase Chain Reaction ( P C R )mentioning
confidence: 99%
“…Because of the high clinical importance of H. pylori infection, numerous diagnostic methods based on nucleic acid technology for its detection in clinical, biological, and environmental samples have been developed (22,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%